Development of Inhibitors against Corrosion and Mineral Salts in Pipes on the Basis of Local Raw Materials - Murotov Akmal Ahmadjonovich; Ibodullayev Ahmadjon Sobirovich (Researchparks Publishing, 2022)
To create inhibitors against corrosion and mineral salts in pipes and to implement them by creating the necessary methods.